PENGARUH GAYA KEPEMIMPINAN, KEPUASAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN UD. MADE CARPENTER GIANYAR - Ni Komang Sekar Mariyani; Ni Made Dwi Puspitawati; Ni Luh Gede Putu Purnawati (EMAS, 2023)
For the sake of realizing the vision and mission, the company seeks to improve employee performance in order to provide good service to the community. One of the factors that influence employee performance is leadership, job satisfaction and work discipline. This study aims to determine the effect partially and simultaneously between leadership, job satisfaction and work discipline on employee performance at UD. Made Carpenter Gianyar. The sample in this study were 32 employees at UD. Made Carpenter Gianyar. In this study, the sample was taken using the saturated sampling method, namely the sample using all members of the population as the research sample. The results of this study indicate that the leadership variable has a positive and significant effect on performance, the job satisfaction variable also has a positive and significant effect on employee performance and work has a positive and significant effect on employee performance. The variables of leadership, job satisfaction and work discipline have a positive and significant effect on employee performance at UD. Made Carpenter Gianyar.